2020
DOI: 10.1038/s41598-020-58264-4
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear Translocation of Glutaminase GLS2 in Human Cancer Cells Associates with Proliferation Arrest and Differentiation

Abstract: Glutaminase (GA) catalyzes the first step in mitochondrial glutaminolysis playing a key role in cancer metabolic reprogramming. Humans express two types of GA isoforms: GLS and GLS2. GLS isozymes have been consistently related to cell proliferation, but the role of GLS2 in cancer remains poorly understood. GLS2 is repressed in many tumor cells and a better understanding of its function in tumorigenesis may further the development of new therapeutic approaches. We analyzed GLS2 expression in HCC, GBM and neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…In the current study, we found that the expression of GLS2 mRNA in the tissues of gastric cancer was significantly lower than in adjacent non-cancer tissue, suggesting that GLS2 downregulation might be associated with the development and progression of gastric cancer. Our data were consistent with the previous reports that GLS2 was repressed in many tumor cells, such as HCCs and glioblastomas ( 16 , 30 ). Szeliga et al demonstrated that GLS2 displayed a significant downregulation in glioblastoma due to DNA demethylation, while CpG methylation was absent in GLS2-expressing adjacent non-cancer brain tissues ( 20 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we found that the expression of GLS2 mRNA in the tissues of gastric cancer was significantly lower than in adjacent non-cancer tissue, suggesting that GLS2 downregulation might be associated with the development and progression of gastric cancer. Our data were consistent with the previous reports that GLS2 was repressed in many tumor cells, such as HCCs and glioblastomas ( 16 , 30 ). Szeliga et al demonstrated that GLS2 displayed a significant downregulation in glioblastoma due to DNA demethylation, while CpG methylation was absent in GLS2-expressing adjacent non-cancer brain tissues ( 20 ).…”
Section: Discussionsupporting
confidence: 94%
“…It is reported that miR-9 can suppress ferroptosis via downregulating GOT1 expression in melanoma (46). In cancer cells, GLS2 upregulation can induce an antiproliferative response with cell cycle arrest (47). Notably, high expression of risk genes, such as CD44, FANCD2 and CHAC1 as well as low expression of NCOA4 were found to be correlated with worse OS in KIRC (21,22), in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Several genes found to be regulated by acidosis after 24 h has been described to affect functional parameter of tumor progression, such as proliferation (e.g., Gls2 [ 37 ]), cell death (e.g., Txnip, Gls2 [ 38 , 39 ] tumor cell migration (e.g., Per3, Ikbke, Txnip [ 40 42 ] and adhesion (e.g., Txnip [ 43 ]) or mitochondrial activity (e.g., Txnip [ 44 ]). Therefore the impact of acidification on these cell functions was analyzed in the tumor models.…”
Section: Resultsmentioning
confidence: 99%